2005
DOI: 10.1038/emm.2005.31
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD9 induces MMP-2 expression by activating p38 MAPK, JNK and c-Jun pathways in human melanoma cells

Abstract: Abbreviations: AP-1, activating protein 1; ECM, extracellular matrix; EMSA, electrophoretic mobility shift assay; JNK, c-Jun N-terminal kinase; mAb, monoclonal antibody; MAPK, mitogen-activated protein kinase; MEK, mitogen-activated protein kinase kinase; MMP, matrix metalloproteinase; RT-PCR, reverse transcriptase-polymerase chain reaction; siRNA, small interfering RNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 21 publications
2
52
0
2
Order By: Relevance
“…It has also been reported that the PI-3K/Akt and nuclear factor-κB (NF-κB) pathways are involved in the regulation of MMP-9 (34). It has been suggested that inhibition of p-ERK1/2 and p-JNK leads to a reduction in tumor cells (35). Recent studies have demonstrated that flavonoid baicalein suppresses adhesion, migration and invasion of MDA-MB-231 human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the PI-3K/Akt and nuclear factor-κB (NF-κB) pathways are involved in the regulation of MMP-9 (34). It has been suggested that inhibition of p-ERK1/2 and p-JNK leads to a reduction in tumor cells (35). Recent studies have demonstrated that flavonoid baicalein suppresses adhesion, migration and invasion of MDA-MB-231 human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, a number of studies have demonstrated the induction of matrix metalloproteinase-2 (MMP-2) by JNK in several tumor forms, including melanomas. 47 In fact, it has been suggested that the multiple MAPK pathways cooperate in the regulation of MMP transcription in response to different signals (reviewed in Westermarck and Kahari 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It cleaves basement membrane collagen IV and V and gelatin, fibronectin, and elastin, (Tryggvason et al, 1992) and plays a crucial role in monocyte extravasation, which is a primary event in inflammation (Watanabe et al, 1993). Its expression is regulated by cytokines, chemokines, and cellular interactions through adhesion molecules (Opdenakker et al, 2001;Hong et al, 2005). In this study, we investigated whether extracellular Hsp70 could be released from living Hsp70 transfectants and induce MMP-9 gene expression.…”
Section: Introductionmentioning
confidence: 98%